Epigenetic determinants of fusion-driven sarcomas: paradigms and challenges - Stanton, Benjamin Z.; Pomella, Silvia (Frontiers in Cell and Developmental Biology, 2024)
We describe recent exciting advances in fusion-driven sarcoma etiology, from an epigenetics perspective. By exploring the current state of the art, we identify and describe the central mechanisms that determines sarcomas ontogenesis. Further, we discuss seminal studies in translational genomics, which enabled epigenetic characterization of fusion-driven sarcomas. Crucial epigenetic mechanism pathways include, but are not limited to, cell cycle and metabolism, core regulatory circuitry, 3dimensional chromatin architectural dysregulation, integration with ATP-dependent chromatin remodeling, and translational animal modeling. Paradoxically, while the precise requirements for oncogenic transformation are highly specific for the fusion partners, the epigenetic mechanisms we as a community have uncovered are categorically very broad. This dichotomy prompts the question of whether the investigation of rare disease epigenomics should prioritize studying individual cell populations, thereby examining whether the mechanisms of chromatin dysregulation are specific to particular tumor. We review the literature focusing on rhabdomyosarcoma, synovial sarcoma, alveolar soft part sarcoma, clear cell sarcoma, undifferentiated round cell sarcoma, Ewing sarcoma, and desmoplastic round cell tumor. The growing number of groundbreaking discoveries in the field, let us anticipate further exciting advances in the area of mechanistic epigenomics and direct targeting of fusion transcription factors in the years ahead.